Necessary light: poems - Fargnoli, Patricia, author; Utah State University Press, publisher (Colorado State University. Libraries, 1999)
Ms. Fargnoli's heartening, disturbing, mature first book is rich with two things poetry can never have enough of: energy and wonder.
Foreword / Mary Oliver -- ONE. How This Poet Thinks -- Hopper's Paintings -- Landscape in Blue and Bronze -- From Eleven Years Later -- Breaking Silence--For My Son -- Naming My Daughter -- Going -- Miniature -- Sea Watchers -- From a Rented Cottage by Winnisquam in Rain -- At the Mystic Aquarium -- Gifts -- Evensong -- The Sleepers -- The Decision -- Nightwork -- Sag Harbor Sundown -- Crossing the Sound -- Pemaquid Beach After a Week Alone -- On Hearing of the Sudden Death of a Friend -- At the Enosberg Falls Cemetery -- Lamentation -- Lightning Spreads Out Across the Water -- Watching Light in the Field -- TWO. In the Winter of My Sixtieth Year -- When I Wake to a Bedroom Filled with Blue Lights -- In the City Without a Name -- Weed in Drought -- Location -- In the Basement of the First Church -- From the Blue Room at the Colony -- Visiting Frost's Grave -- Boundaries -- Winter Sky over Cheshire County, New Hampshire -- Starry Night -- Fall Garden and the Weather Coming In -- Invocation -- The Reading: University College, Galway -- Near Galway -- Dublin Beggar -- Pilot Glasses -- Roofmen -- Naming -- Anniversaries -- Still Water -- Letter from Cranberry Island.
Keywords: American poetry